2014
DOI: 10.1097/cji.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Generation of Interstitial and Langerhans Cell-like Dendritic Cell Subset–based Vaccines for Hematological Malignancies

Abstract: Autologous, patient-specific, monocyte-derived dendritic cell (MoDC) vaccines have been successfully applied in the clinical studies so far. However, the routine application of this strategy has been hampered by the difficulties in generating sufficient numbers of DC and the poor DC vaccine quality because of pathology or prior treatment received by the patients. The immunotherapeutic potential of other subsets of DC has not been thoroughly investigated because of their rarity in tissues and difficulties assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Thus, UCB could be exploited as an additional source for the generation of allogeneic DCs. UCB-derived DCs have been used in the pilot phase of clinical trials as well, in hematological disorders like AML, as a therapeutic agent to increase the survival of patients [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, UCB could be exploited as an additional source for the generation of allogeneic DCs. UCB-derived DCs have been used in the pilot phase of clinical trials as well, in hematological disorders like AML, as a therapeutic agent to increase the survival of patients [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, LCs, presumably via a mechanism that involves IL-15, are far more superior than dermal DCs and moDCs (Romano et al, 2012;Hutten et al, 2014) in terms of their capacity to stimulate antigen-specific CTL immunity. This explains the impetus behind the recent efforts to design new protocols for the generation of DCs with LC-like features (Hutten et al, 2014).…”
Section: B Pharmacological Aspects Of Dendritic Cell-based Cancer Immentioning
confidence: 98%
“…As discussed above, LCs, presumably via a mechanism that involves IL-15, are far more superior than dermal DCs and moDCs (Romano et al, 2012;Hutten et al, 2014) in terms of their capacity to stimulate antigen-specific CTL immunity. This explains the impetus behind the recent efforts to design new protocols for the generation of DCs with LC-like features (Hutten et al, 2014). Such LC-type, IL-15-expressing DCs can be generated from CD34 + hematopoietic progenitor cells using specific differentiation factors (Romano et al, 2011) or from CD14 + monocytes by replacing IL-4 with IL-15 (Mohamadzadeh et al, 2001;Anguille et al, 2009Anguille et al, , 2013.…”
Section: B Pharmacological Aspects Of Dendritic Cell-based Cancer Immentioning
confidence: 98%
“…To this end, Hutten et al [40] recently reported a method for the generation of mature CD1a þ mDC and CD207 þ Langerhans cells (LC) from UCBderived CD34 þ HPCs. These cells display potent expansion induction of minor histocompatibility antigen (MiHA)-specific T cells isolated from PB of leukemia patients, as well as priming of naive MiHAspecific T cells.…”
Section: Cb-derived DC Vaccinesmentioning
confidence: 99%